-2(3x-7)=36

Simple and best practice solution for -2(3x-7)=36 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(3x-7)=36 equation:


Simplifying
-2(3x + -7) = 36

Reorder the terms:
-2(-7 + 3x) = 36
(-7 * -2 + 3x * -2) = 36
(14 + -6x) = 36

Solving
14 + -6x = 36

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-14' to each side of the equation.
14 + -14 + -6x = 36 + -14

Combine like terms: 14 + -14 = 0
0 + -6x = 36 + -14
-6x = 36 + -14

Combine like terms: 36 + -14 = 22
-6x = 22

Divide each side by '-6'.
x = -3.666666667

Simplifying
x = -3.666666667

See similar equations:

| 16+4x+3=-2x-(-6x)+12-(-7) | | 5x-100=-2x+40 | | 7x-4=-11x+6 | | 25x/45=-67 | | 1+7x=-5x-23 | | -4(1+k)=-3-3k | | (3y^2-8y+1)-(2y^2-8y+8)= | | -37-x=35-9x | | -3r-12=4-r | | x-7/6=2 | | X*4=100 | | 10n+5-8n-3=12 | | 2(m+3)= | | 9-5/8x=10 | | 12-15x(-5)= | | x^2+22x=-84+10x | | 7n+29=8 | | -12x^3+9x^2=0 | | -26+4= | | -4=a-10u | | 8+x=-(x+8) | | -5-10x^2=-68 | | G=3j+4 | | y=7(-8)-26 | | -5+48= | | 16-3n=1-8n | | y=-5(-8)-35 | | (2z-7)(6+z)=0 | | y=3(-8)-72 | | 0.6t=0.9+0.4t | | 3(4z-7)=21+12z | | h/2=13.44 |

Equations solver categories